A study on the optimal air, load and source side temperature combination for a variable air and water volume ground source heat pump system. (September 2020) - Lin, Yaolin; Wang, Huan; Hu, Pingfang; Yang, Wei; Hu, Qiushi; Zhu, Na; Lei, Fei
Highlights: Ground source heat pump with variable air volume system was modeled. Air side, demand side and source side temperature optimization was conducted. COPs were improved from 2.17 to 4.46 in summer, and from 1.46 to 3.99 in winter. Optimal air side and water side temperatures differ from design recommendations. Abstract: In this paper, mathematical models on the energy and exergy performance of a variable air and water volume (VAWV) ground source heat pump (GSHP) system serving an office building in Wuhan, China, were developed. The study aims at investigating the optimal combination of supply air temperature, load side and source side supply and return water temperature to maximize the energy and exergy performance of the whole system. To find the optimal control solution for the system, Latin Hypercube Sampling Method (LHSM) was used to create data sets for training the Back Propagation Neural Network (BPNN) models to predict the energy and exergy performance and couple with Genetic Algorithm (GA). It was found that the system coefficients of performance (COPs) for the original system under constant air and water volume (CAWV) in summer and winter were 2.17 and 1.46, respectively. The associated exergy efficiencies were 7.60% and 3.93%, respectively. The coefficients of performance (COPs) for the variable air and water volume (VAWV) system under normal operation in summer and winter were 3.70 and 3.48, respectively, while their associated exergy efficiencies were improved to 11.43% and 4.12%, respectively. The coefficients of performance (COPs) under optimal control, however, can reach 4.46 in summer and 3.99 in winter and the exergy efficiencies could reach 13.87% and 7.27%, respectively.